Flow induced dispersion analysis rapidly quantifies proteins in human plasma samples1. Issue 13 (7th July 2015) - Poulsen, Nicklas N.; Andersen, Nina Z.; Østergaard, Jesper; Zhuang, Guisheng; Petersen, Nickolaj J.; Jensen, Henrik
<x xml:space="preserve">Abstract</x> The change in dispersion of an indicator molecule (ligand) interacting with an analyte is used as an accurate measure of analyte concentration.